Financial Management with the Sakinah Finance Model for Coastal Communities - Eny Latifah (Asian Journal of Management Analytics, 2022)
The majority of household financial management in the North Coast community is carried out by housewives. North coast communities are closely related to the type of livelihood they have. The treatment of the provision of finance in each household is very varied. This can be seen from the point of view of the amount of income, hobbies, lifestyle and passion that each household has. Communities on the north coast of Java tend to prioritize primary needs over secondary and tertiary needs. The coastal community of Paciran Lamongan village prioritizes managing income, managing needs, managing contingencies, managing dreams and managing surplus/deficit.